Insect pests intercepted in imported germplasm during 2013 and 2014 - Gupta, Kavita; Bhalla, Shashi; Singh, S P; Meena, D S (Indian Journal of Plant Protection, 2020)
Quarantine examination of 2,07,444 exotic seed samples and vegetative propagules (834) of various crops during 2013 and 2014 revealed infestation by insects in 1,505 samples including 539 instances of hidden infestation. Several pests were intercepted during visual examination including storage beetles and weevils. Interception of several alien insects was very significant as these pests were not known to occur in India which included Acanthoscelides desmanthi in Desmanthus spp. from Colombia; A. obtectus in Lathyrus sativus from Lebanon, Bruchus dentipes in Vicia faba from Lebanon; B. ervi in Pisum sativum and L. sativus from Lebanon and B. tristis in Lens culinaris from Lebanon. All necessary quarantine protocols were followed before releasing the germplasm consignments to the consignees with respect to the insect infestations in general and pests of quarantine significance in particular.